Fetal movements in mid-pregnancy and their relationship to neonatal competency - S. H. Irwin-Carruthers (AOSIS, 1995)
The aim of the study was to investigate the relationship between fetal movement and neonatal behaviour, as well as to compare the fetal movement patterns and neonatal competencies of black and white infants. The sample for the pilot trial consisted of 12 mothers and their infants, selected at between 10 and 12 weeks of gestational age. The black sample and part of the white sample was drawn from the low-risk population attending the booking clinic of St Monica's Hospital; the rest of the white mothers were drawn from the private sector. Nine mothers satisfied the criteria throughout the trial. Two had to be excluded when their pregnancies were terminated and a third was excluded due to epilepsy. Fetal movement was recorded by ultrasound scanning at 20/52 gestational age, recorded on videotape. All infants were born at full term by normal vertex delivery. The Brazelton neonatal behavioural assessment scale (BNBAS) was performed between 12 and 36 hours post-birth. This assessment was also videotaped. Test-retest reliability for counting and classifying fetal movements was established at 99,45(SF=1.05). Sequential and isolated movements predominated and the proportion of sequential and isolated movements was related to the total number of fetal movements. Higher FM scores were also related to more optimal scores on the BNBAS in the neonatal period. The black infants tended to show more mature patterns of fetal movement than white infants. The black infants also scored better on the BNBAS in relation to optimal postural tone, motor maturity and good orientation/alertness. The number of subjects in the pilot trial was too small for statistical analysis, but the results justify continuation of the main trial.